2019
DOI: 10.5539/elt.v13n1p63
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phonetic and Phonological Constraints of Saudi EFL Learners

Abstract: This study explores the pronunciation difficulties experienced by Saudi EFL learners at Jouf University (JU) in the north of Saudi Arabia. To achieve this purpose, two main instruments were implemented: an experiment of pronunciation sensitivity response and two interview formats. The sample of this study was selected randomly and consisted of (n=20) students studying English major in their sixth level at JU, and (n=10) English language instructors from the same institution. A mixed-method approach was employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Ababneh (2018) also pointed out that the Saudi EFL learners confused the vowel /e/ sound with /i/. The same result was also reported by Ali (2013); Kalaldeh (2016); Al-Rubaat and Alshammari (2020). This difficulty in production may further lead to difficulty in the perception of these vowels.…”
Section: Discussionmentioning
confidence: 63%
“…Ababneh (2018) also pointed out that the Saudi EFL learners confused the vowel /e/ sound with /i/. The same result was also reported by Ali (2013); Kalaldeh (2016); Al-Rubaat and Alshammari (2020). This difficulty in production may further lead to difficulty in the perception of these vowels.…”
Section: Discussionmentioning
confidence: 63%
“…During the last decade, researchers investigated pronunciation problems made by EFL Arab learners in terms of learning difficulties in English phonology. Al-Rubaat & Alshammari (2020) discovered that EFL learners had difficulty correctly pronouncing the first three consonant clusters and the final three in English. He concluded that learners were mistakenly pronouncing these clusters as employed reduction, substitution, or deletion as alternate methods.…”
Section: Jahara and Abdelradymentioning
confidence: 99%
“…The researchers of that study achieved their goal by implementing two main instruments: a pronunciation sensitivity response experiment and two interview formats. (Al-Rubaat & Alshammari, 2020). They found that: initial consonant cluster, ending consonant cluster, multi-syllabic words, novel sounds, vowels, and voiced or voiceless phonemes were among the six phonetic and phonological problematic patterns experienced by EFL students (Al-Rubaat & Alshammari, 2020).…”
Section: Jahara and Abdelradymentioning
confidence: 99%
“…In spite of the crucial role of pronunciation in oral communication, Saudi English as a foreign language (EFL) learners' English pronunciation is poor (Al-Rubaat & Alshammari, 2020;Naser & Hamzah, 2018). Although Saudi EFL students learn the English language for six years at school (Shehzad, Alghorbany, Lashari, & Lashari, 2019a;Shehzad, Alghorbany, Lashari, Lashari, & Razzaq, 2019b;Shehzad, Razzaq, Dahri, & Shah, 2019c), they still face difficulties in communication and pronunciation (Naser & Hamzah, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that Saudi EFL learners' poor pronunciation could be attributed to several factors including first language interference (Al-Rubaat & Alshammari, 2020; Hago & Khan, 2015), incompetent teachers (Naser & Hamzah, 2018), ineffective teaching methods (Alfehaid, 2015) and learners' attitudes towards learning pronunciation (Naser & Hamzah, 2018). However, there is scarcity of research in the psychological factors that can affect the pronunciation skills of Saudi EFL learners (Al-Rubaat & Alshammari, 2020).…”
Section: Introductionmentioning
confidence: 99%